DAA-Based Treatment for HIV–HCV-Coinfected Patients: Analysis of Factors of Sustained Virological Response in a Real-Life Study. Issue 4 (May 2020) - Alessio, Loredana; Onorato, Lorenzo; Sangiovanni, Vincenzo; Borrelli, Francesco; Manzillo, Elio; Esposito, Vincenzo; Simeone, Filomena; Martini, Salvatore; Capoluongo, Nicolina; Leone, Sebastiano; Filippo, Giovanni Di; D'Abbraccio, Maurizio; et al.
Background: The aim of the present study was to evaluate in HIV-infected patients treated with a direct-acting antiviral agent (DAA)-based regimen the variables associated with sustained virological response (SVR) and the trend in biochemical parameters and clinical events during and after DAA regimen. Methods: We performed a multicentre retrospective cohort study, enrolling all 243 HIV–HCV-coinfected adult patients treated with DAAs between January 2015 and December 2018 in one of the nine participating Infectious Disease Centers in southern Italy, eight in Campania and one in Apulia. Results: Of the 243 patients enrolled, 233 (95.9%) obtained an SVR at 12 weeks (SVR12). Of the 10 patients with non-SVR, 7 were tested for NS3, NS5A and NS5B resistance-associated substitutions (RASs) by sequencing analysis and 6 showed at least 1 major RAS in 1 HCV region (all in NS5A, 2 in NS5B and 1 in NS3). Comparing the 233 patients achieving SVR and the 10 non-achievers, no variable was independently associated with non-SVR. During and after DAA regimen, no modification in the biochemical parameters and clinical events was observed; however, the serum cholesterol and low-density lipoprotein (LDL) levels showed an increase (from 159 ±41.3 mg/dl at baseline to 174 ±44.5 mg/dl at week 12 after stopping treatment, P <0.001, and from 92 ±34.6 mg/dl to 109.4 ±73.7 mg/dl, P =0.002, respectively). Conclusions: The treatment with DAAs led to a high SVR12 rate in HIV–HCV-coinfected subjects, irrespective of epidemiological, clinical or virological characteristics. However, the DAA regimen was associated with an increase in total- and LDL-cholesterol, to be taken into account in the management of HIV infection